UN PRIMAR AL CULTURII, UN PRIMAR EUROPEAN - COLESNIC, Iurie (BIBLIOPOLIS, 2020)
Carol-Ferdinand Schmidt (25.06.1846, Balti – 9.04.1928, Chisinau) was the most long-lived mayor of our city, during 25 ages. He transformed a provincial town in a real capital of the province (gubernia). Carol Schmidt, German by origins, became mayor by accident. He was investigator and after the death of his brother-in-law, Clementie Sumanschi, the Municipal Council (Duma) has appointed him a mayor. Being mayor he modernized the town, changing the wood pavement to cobble-stone road, introducing the tramway and the electricity, waterline and sewerage system, the first art exhibitions, installing monuments, building: The Chisinau City Hall, The Museum of Nature, the Bank of Bessarabia, schools etc. He dismissed from office after the pogrom in 1903, declaring that he not want to be a mayor of such wild city. However, the townspeople decided to name the city street where was situated the mayor’s house by his name (actually – street Varlaam).